Study on permafrost thermal stability and disturbance of the Mohe-Daqing oil pipe and its accompanying road of China-Russia Crude Oil Pipeline - DING, LIN; YANG, YANG; LIU, PING HAI (Journal of Engineering Research, 2020)
The Mohe–Daqing oil pipeline (MDOP) of China–Russia crude oil pipeline (CRCOP) goes through a 441 km permafrost in high-latitude regions, the most critical problem of which is the thawing settlement of the oil pipe. Global warming effect, oil temperature, and construction technology causes the increase of ground temperature and accelerates the degradation of permafrost. The influence of geohazards on the existing CRCOP and its accompanying road was investigated in this study, which showed that the current engineering had been affected by freezing-thawing influence. It would be more serious for the thermal disturbance between each other. In view of this problem, the thermal stability of the oil pipe and accompanying road was simulated based on the MDOP, considering various scenarios of different oil temperatures, whether global warming is considered or not, whatever the thermal insulation layer is and regardless of the different distances from the accompanying road. The numerical results indicate that the oil temperature had considerable influence on the thawing rate of permafrost. Placing the thermal insulation material around the oil pipe can effectively mitigate or even control the degradation of permafrost. With this measurement, the thaw depth has remained stable after 5 years of construction, and had been controlled within 3.0 m when the thermal insulation thickness reached 8.0 cm. The accompanying road can also have an adverse effect on the permafrost for its thermal interaction with the oil pipe. The larger the distance, the lesser the thermal disturbance. Therefore, the thermal stability of MDOP can positively adopt a suitable oil temperature for thermal insulation thickness, along with an optimized distance away from the accompanying road as well. This study would also provide an essential theoretical and technological support for the design of oil pipeline in other permafrost regions.